PERLINDUNGAN HUKUM BAGI KORBAN TINDAK PIDANA KEKERASAN DALAM RUMAH TANGGA DI KOTA PALOPO - Sri Rahayu Amri (Lembaga Penerbit dan Publikasi Ilmiah (LPPI) Universitas Muhammadiyah Palopo, 2017)
The ideal legal protection is not solely focused on the implementation of legislation, although in reality, the legal protection of the tendency is not implemented as expected by the community, as some interpret the judge's decision. Domestic violence is any form of violence perpetrated by husbands, wives, other family members who result in physical, psychological, sexual and economic harm, including threats, deprivation of liberty occurring in a household or family.This study aims to see the form of legal protection against victims of domestic violence, and then analyze the factors that influence the effectiveness of the prevention of domestic violence, which then look at the extent of the effectiveness of the prevention of domestic violence against victims of violent crime In particular households and the general publicThis research is a descriptive study with a juridical-empirical approach that examines the rules of positive law in order to get answers to the existing problems by linking with facts or phenomena about Domestic Violence. This study is a doctrinal and non-doctrinal combines normative research and empirical research using annotations through library research methods and field research method. Keywords : Legal Protect ion, Crime Victims, Domestic Violence